In‐Liquid Micromanipulation via a Magnetic Microactuator for Multitasking - Dineshkumar Loganathan; Chia‐Hsin Cheng; Po‐Wei Wei; Chia‐Yuan Chen (Small Science, 2025)
Small‐scale actuators capable of performing multiple tasks are crucial for the advancement of microfluidic technologies. These actuators enable high‐throughput operations and support integrated solutions across a wide range of applications. In this study, a multipurpose magnetic microactuator (MMA) is developed with two pairs of magnetic arms controlled externally through a custom‐built electromagnetic system. To enhance navigational precision, two circular magnetic sections named “mobility components” are integrated into the MMA's design. The multitasking capability of the MMA is demonstrated through distinct applications, including particle manipulation, microassembly, micromixing, and flow conveyance. In particle manipulation, the MMA is controlled to grasp a total of eight particles from different locations in a single cycle within 46 s. During the assembly process, two 2D planar micro‐objects are sequentially loaded, transported, and assembled in the designated assembly unit. For fluid flow control, the distinct motions of the MMA are observed to enhance the mixing performance with an efficiency of 65% within 20 s. In addition, the dye conveyance efficiency is observed to reach 85% for the MMA's navigational distances of 10 mm in 30 s. These results demonstrate the MMA's capacity for synergistic multitasking with increased throughput, establishing it as a foundation for future microfluidic actuators.